พฤติกรรมตามแนวคิดการบริโภคที่ยั่งยืนของประชาชนในอำเภอเมืองเชียงใหม่ ต่อการซื้อจักรยาน - อิศรินยา ปริสุทธิกุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study is intended to study behavior according to sustainable consumption concept of People in Mueang Chiang Mai district towards purchasing Bicycles. Questionnaires were used to collect data from 300 of riders who lived in Mueang Chiang Mai selected by quota sampling based on main purpose of use bicycles for Vehicle and Recreation. The analysis was made based on descriptive statistics and inferential statistics. The results of general information showed of the respondents were male, aged between 5-34 years old, Majority of the respondents were single with the bachelor’s degree, worked as private company employees. Most of them had average income between 20,001-30,000 baht. purchased mountain bike, Their main purposed for exercise and used the information that they had to make a decision and also influenced by themselves, purchased on January-March from Cycling shops. Most of respondents have one bicycle with the average cost of less than 10,000 baht. Also found that internet had influence on decision making for respondents. Considering marketing mix factors; according to sustainable consumption concept, which were the most important factors influenced the decision of respondents towards purchase bicycle, Product factors were capacities of bicycle, Price factors were suitable price with product quality, Place factors were the reliability of dealer and Promotion factors were media advertising and campaigns . Respondents agreed to sustainable consumption concept with the total mean of 3.6928. This mean was used to classify respondents into 2 groups which were general consumers 51 percent and sustainable consumption consumers 49 percent. This study found out that there were statistically significant relationship of consumer profiles; only aged between both consumer groups at a significance level of 0.05. Furthermore, there were also statistically significant difference in the importance of marketing mix factors according to sustainable consumption concept; Product factors are Brand, exterior design, capacity, cost saving, the quality guarantee, alternative vehicles, reduce pollution, second hands bicycle’s parts for sale, Price factors are suitability of price, various of price, maintenance, suitability price for economics, re-selling as used bicycle, Place factors are reliability of dealer, branch, easy access to channel, environment and nature conservation, shop location, Promotion factors are advertising and public relation, campaigns, information provided by salesperson, corporate social responsibility, social and environmental responsibility, trading for new bicycle.